Dear Mr. Buffett : what an investor learns 1,269 miles from Wall Street - Tavakoli, Janet M. (Finance professional collection, 2009)
"Janet Tavakoli takes you into the world of Warren Buffett by way of the recent mortgage meltdown. In correspondence and discussion with him over 2 years, they both saw the writing on the wall, made clear by the implosion of Bear Stearns. Tavakoli, in clear and engaging prose, explains how the credit mess happened beginning with the mortgage lending Ponzi schemes funded by investment banks, the Fed bailout and its impact on the dollar. Through her narrative, we hear from Warren Buffett and learn how his enduring principles caused him to see the mess that was coming well in advance and kept him and his investors well out of the way"--Resource description page